Sharia governance and corporate social responsibility as instruments to achieve asean food vision 2025 - Katamsi, Etom; Afif, Ahmad; Sabbahatun, Sri; Amalia, Euis; Mufraini, M. Arief; Hasan, Asyari (al-Uqud : Journal of Islamic Economics, 2024)
This study aims to identify strategies to achieve the ASEAN 2025 vision in the agriculture sector using sharia governance and Corporate Social Responsibility (CSR) schemes. Therefore, this research will use a mixed method for data analysis. The sample is from Islamic banking in Indonesia, Malaysia, and Singapore. In addition, the dependent variable is taken from ASEAN agriculture statistics for 2018-2022. The results have explained that CSR indicators from the Islamic Social Reporting theory in the agriculture sector are widely developed in Indonesia. It is also supported by Law No. 4 of 2023 on P2SK in formulating changes in the role of sharia governance and CSR. In addition, financial, product, employee, community, and environmental indicators need to be further improved by Islamic banking through additional distribution in financing and investment in the agriculture sector. There are several policy recommendations for all ASEAN stakeholders and Islamic banking. ASEAN countries need to focus their economic vision on the agriculture sector. In addition, Islamic banking in ASEAN countries can implement sharia governance and CSR schemes in corporate governance and economic policies. Therefore, it must also be supported by good governance in the Sharia governance scheme.